Model Komunikasi Antar Pribadi Caregiver Dengan Penderita Alzheimer - Mira Renata (Program Studi Hubungan Masyarakat Politeknik LP3I, 2022)
Growing old is a natural law in the story of human life that is destined to live long, where physically as we get older, humans will experience a decrease in the function of tools, as well as the elderly who suffer from Alzheimer's. The purpose of this study was to find out communication techniques, types of message delivery and find out why interpersonal communication is important when there is a fight for family members who suffer from Alzheimer's, because each family has its own ways and habits in daily activities. The theory used in this study uses the theory of Interpersonal Communication, Symbolic Interaction, I-Thou Theory and Therapeutic Communication. The method used in this study uses a qualitative descriptive approach. A qualitative approach is considered. The method in this study uses qualitative methods, because research is a scientific activity that is carried out through a long process for the purposes of gathering information, drawing conclusions about certain phenomena in empirical symptoms. The results of the study It is necessary to have different communication techniques when dealing with Alzheimer's sufferers, communication techniques include informative communication, persuasive communication, command communication and human relations and these four components are one of the techniques used by caregivers. In addition to techniques in conveying communication, it turns out that the types of message delivery carried out by family members with Alzheimer's sufferers are also different, namely by using verbal and nonverbal communication, and the most important thing in dealing with Alzheimer's patients is to think of them like the elderly in general. , and in Communication Studies it is better known as interpersonal communication or face-to-face communication, where this communication is usually a series of message exchanges between two individuals, namely between caregivers and Alzheimer's sufferers and interpersonal communication becomes a very helpful communication activity between caregivers and Alzheimer's. Alzheimer's.